Congenital Hypothyroidism: An Unusual Combination of Biochemical Abnormalities - Ruchi Mantri; S. B. Bavdekar; Sushma U. Save (Case Reports in Pediatrics, 2016)
A forty-five-day-old female infant presented with prolonged jaundice with clinical features suggestive of congenital hypothyroidism (CHT). On investigations, the infant was noted to have indirect hyperbilirubinemia (13.8 mg/dl) with increased levels of AST (298 IU/dl) and ALT (174 IU/dl) in the serum. The child had low levels of free T3 (<1 pg/ml) and free T4 (0.4 ng/dl) secondary to thyroid agenesis detected on radionuclide scan and ultrasonography of the neck and raised levels of TSH (>500 microIU/ml) in the serum. The combination of indirect hyperbilirubinemia and raised levels of hepatic transaminases has not been reported in babies with CHT. Following institution of oral thyroxin therapy, the serum bilirubin levels ameliorated (2.9 mg/dl) considerably by 15 days of therapy and the serum levels of AST (40 IU/dl) and ALT (20 IU/dl) got normalized. The case demonstrates that raised levels of hepatic transaminases can occur in infants with CHT and these can resolve just with thyroxin therapy, obviating the need for extensive investigative laboratory work-up.